How does trust impact e-commerce adoption among Vietnamese vendors: PLS-SEM approach - Phan, Hai Hong; Nguyen, Cuong Quoc; Nguyen, Anh Minh-Tu (Journal of Social Economics Research, 2025)
With the explosion of Industry 4.0, e-commerce plays a pivotal role in developing vendors in Vietnam, especially since the demand for online shopping is rapidly increasing and becoming familiar to customers. Extending the Technology Acceptance Model (TAM) framework, a widely accepted theoretical framework in technology adoption, this study investigates the significant determinants of adopting e-commerce platforms among Vietnamese vendors. The research identifies Perceived Usefulness (PU), Perceived Ease of Use (PE), Trust (TR), and Data Security (DS) as the determinants shaping adoption behavior by focusing on their effects on PU and PE. The collected data was analyzed using a quantitative approach, employing Partial Least Squares Structural Equation Modeling (PLS-SEM) data from 515 Vietnamese vendors. The study presents the results by measuring the intention to use e-commerce, analyzing the data, and adjusting the scale of the intention to use e-commerce by surveying the research subjects with four factors and twenty observed variables. This process involved rigorous statistical analysis and validation techniques to ensure the reliability and validity of the findings. The results indicate that Trust is a vital mediating factor in the relationship between PU, PE, and DS, as well as behavioral intention, emphasizing its centrality in e-commerce adoption. Trust acts as a bridge that enhances the perceived usefulness and ease of use of e-commerce platforms while mitigating data security concerns. Data security emerges as a major driver that gains Trust and simultaneously reduces the perception of fraud and data breaches. Policymakers, platform providers, and business leaders can leverage the insights from this research to foster Trust, ensure data security, and enhance regulatory knowledge for sustainable e-commerce adoption. By integrating external factors into the TAM framework, this study significantly contributes to the literature on e-commerce adoption, paving the way for open innovation in e-commerce in Vietnam and other emerging markets in Asia.